Analisis Data Penerimaan, Biaya, dan Pendapatan Usahatani Padi Sawah di Desa Matahori Kecamatan Padangguni Kabupaten Konawe - Jumran Jumran; Sarty Syarbiah; Leni Saleh; Tauwi Tauwi (JINGLER : Jurnal Teknik Pengolahan Pertanian, 2025)
This study aims to analyze the income from rice farming in the rice fields of Matahori Village, Padangguni Subdistrict, Konawe Regency. The sample used in this study consists of 20 farmers, selected through a census. This research is descriptive quantitative in nature, focusing on the analysis of data regarding revenue, costs, and income from rice farming in Matahori Village. The analytical tool used in this study is income analysis, which calculates the difference between the revenue earned by farmers and the costs incurred during the production process. The results of the study show that the total income from rice farming in Matahori Village amounts to IDR 672,232,000. The average income per farmer is IDR 33,611,600. This significant income indicates that rice farming in Padangguni Subdistrict has good economic potential for the local community. It shows that rice farming can make an important contribution to improving the economy, especially for farmers who manage their land well. However, the study also identifies several costs that farmers must incur, such as the costs of purchasing seeds, fertilizer, pesticides, and labor. These costs certainly affect the total income received by farmers. Nevertheless, the income derived from rice farming still shows a profitable potential for farmers, given the high income generated. Overall, the results of this study indicate that rice farming in Matahori Village, Padangguni Subdistrict, makes a significant contribution to the local economy. With proper management, rice farming has the potential to continue growing and providing greater welfare for farmers. Success in managing this agricultural business can serve as an example for other areas in improving the economy based on agriculture.